IMPROVEMENT OF CLASS VIII B STUDENTS IN SMP IT PELITA PROBOLINGGO THROUGH THE USE OF CHART - Lativa Qurrotaini (Journal Learning Geography, 2020)
Charts are studies that have been successful and are widely used in educational research. This learning is a learning effort that trains them to construct their own material into a chart. The chart contains material that links one sub-material to another with the help of labels as a link so that it becomes a meaningful proposition. The formulation of the problem in this study is how learning through the use of charts can improve social studies learning outcomes for class VIII SMP IT Pelita Probolinggo.Chart merupakan pembelajaran yang telah berhasil dan banyak digunakan dalam penelitian pendidikan. Pembelajaran ini merupakan upaya pembelajaran yang melatih mereka untuk  mengkonstruk sendiri materi yang mereka peroleh menjadi sebuah bagan. Dalam bagan tersebut memuat materi yang mengkaitkan antara sub materi yang satu dan yang lain dengan bantuan label sebagai penghubung sehingga menjadi sebuah proposisi yang bermakna. Rumusan masalah dalam penelitian ini adalah bagaimana pembelajaran melalui penggunaan Chartdapat meningkatkan hasil belajar IPS kelas VIII SMP IT Pelita  Probolinggo.